Penggunaan Pendekatan Keterampilan Proses Untuk Meningkatkan Pemahaman Siswa Tentang Konsep Energi Bunyi Di Kelas Vi Sd Negeri 110 Pompanua Kabupaten Bone - asiah asiah (Universitas Negeri Makassar, 2019)
The problems in this study are as follows: whether learning process approaches can improve students' understanding of the concept of sound energy in Class VI SD Negeri 110 Pompanua Kab. Bone. Sources of data in this study are research personnel consisting of students and teachers. The types of data obtained are quantitative and qualitative data consisting of learning outcomes tests, observations, evaluations, reflections and interview results. The results of the study show that there is an increase which means both the activities of teachers and students during the learning process and the results of learning to understand the concept of sound energy. This increase can be seen in each cycle of cycles. Cycle one level of student mastery is sufficient (C), cycle two levels of mastery of good students (B). From the results of the research and discussion, it was concluded that learning using a process skills approach that could improve students' understanding of sound energy concept teaching in 110 Public Schools in Pompanua was as follows: (a) Observing, (b) Classifying / calcifying, (c) Interpreting, (d) Planning research, (e) Predicting, and (f) Applying, (g) Communicating, and (h) Evaluation. The Researcher's suggestion is for elementary school teachers to use the process skills approach as one of the alternatives to improve the understanding of concepts in sound energy learning in elementary schools.